Comparison of the Effect of Dog, Surgeon and Surgical Procedure Variables on Improvement in Eight-Week Static Weight-Bearing following Tibial Plateau Levelling Osteotomy - Wilson, Megan L.; Roush, James K.; Renberg, Walter C. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objective The purpose of this article was to compare the effect of surgeon and tibial plateau levelling osteotomy (TPLO) procedure variations on the outcome of TPLO in naturally occurring cranial cruciate ligament disease.Materials and Methods Records from 142 dogs that had a TPLO procedure were reviewed for information regarding surgical procedure, status of meniscus at the time of surgery, surgeon identity, ACVS diplomate or resident, meniscal release, progression of healing at the progress evaluation based on radiographic interpretation and complications encountered. The primary outcome measure was static force on the affected limb at re-evaluation (42–84 days postoperatively) on a PetSafe Stance Analyzer.Results Re-evaluation tibial plateau angle (TPA) was negatively and significantly correlated with improvement (r = −0.2132, p = 0.013). Postoperative and re-evaluation TPA were all significantly correlated with one another. The amount of TPA change from initial to immediate postoperative values was significantly correlated with the preoperative TPA (r = 0.628, p < 0.001). Surgeon, surgical experience, arthrotomy, meniscal damage, meniscal intervention, complications, postoperative TPA and preoperative TPA had no significant effect on weight-bearing at recheck.Clinical Significance TPLO show improvement of 4.58% body weight on the affected limb at 6 to 12 weeks rechecks on a Stance Analyzer. Surgeon, surgical experience, arthrotomy, meniscal damage, meniscal intervention, complications, postoperative TPA and initial TPA have no effect on this measurement of surgical outcome.
Keywords: cranial cruciate ligament; cruciate ligament disease; dog; tibial plateau levelling osteotomy; static weight bearing